Hypereutrophication, Hydrogen Sulfide, and Environmental Injustices: Mechanisms and Knowledge Gaps at the Salton Sea - Diego Centeno; Alejandra G. Lopez; Aydee Palomino; Juliana Taboada; Ryan Sinclair; Quinn Montgomery; Consuelo Marquez; Migdalia N. Sanchez; Isabella B. Arzeno‐Soltero; Mara A. Freilich (GeoHealth, 2025)
Abstract The Salton Sea, California's largest lake, is undergoing significant environmental degradation, which has adverse health effects on nearby rural communities, primarily Latinx and Torres Martinez Desert Cahuilla Indian. Over the past two decades, the lake's water levels have steadily dropped. Water conditions in the Sea, characterized by low oxygen and high nutrient levels, favor the production of hydrogen sulfide (H2S). This study investigates the connection between the Sea's changing conditions, particularly the worsening water quality, and H2S emissions using air quality and water quality data collected since 2013 and 2004, respectively. H2S concentrations often exceed California's air quality standards, particularly in areas near the Sea during summer months. Wind patterns substantially impact detection of H2S. When wind is blowing from the Sea toward communities with sensors, located to the northwest of the Sea, H2S is detected significantly more often. Current monitoring efforts underestimate the frequency and distribution of H2S that exceeds air quality standards. An air sensor deployed in shallow water over the Salton Sea by a community science program detected substantially higher concentrations of H2S, particularly when wind was blowing over exposed sediment and shallow water, suggesting that these are a significant and overlooked H2S source at the Salton Sea. These findings highlight the need for improved air quality monitoring and more effective environmental management policies to protect public health in the region. The study emphasizes the importance of community‐led solutions and provides insights relevant to other regions experiencing similar environmental crises.